Gingival retraction: thickness measurement and comparison of different cords - Greco, Cinthya Massari; Anfe, Taciana Emília de Almeida; Caneppele, Taciana Marco Ferraz; Agra, Carlos Martins (Brazilian Dental Science, 2015)
Objective: To measure the thickness of five different brands of gingival retraction cords and verify whether there would be a relationship among the sizes and their numbers and a coherent increasing from the thinnest to the largest thickness. Material and Methods: the following cords were evaluated: Gengiret(G), Retraflex(RF), Retractor(RT), Ultrapack(UP), and Pro Retract(PR). Pieces of the cords were placed beside a metallic ruler and photographed standardly regarding to the distance and light. The measurements of the thickness were performed through imaging software (Adobe Photoshop CS6 - Adobe Systems, San Jose, CA, USA). The obtained data were submitted to statistical analysis (one-way ANOVA and post hoc Sheffé test (p = 0.05)). Results: The number and the thickness of the cords mismatched for most of the brands evaluated. Two brands (UP and PR) showed a thickness increasing that mismatched the size increasing between the thinnest and largest cord. Conclusion: The number assigned to the cords by the manufactures did not correspond to a standard thickness, so that the dentist must observe the risk of using cords from different brands during gingival retraction procedures during techniques requiring more than one retraction cord.